Ultimate modulation bandwidth of 850 nm oxide-confined vertical-cavity surface-emitting lasers. (October 2015) - Bobrov, M A; Blokhin, S A; Maleev, N A; Kuzmenkov, A G; Blokhin, A A; Zadiranov, Yu M; Troshkov, S I; Ledentsov, N N; Ustinov, V M
Abstract: Complex influence of photon lifetime (controlled by the mirror loss) and aperture size on the performance of 850 nm InGaAlAs oxide-confined vertical-cavity surface-emitting lasers (VCSELs) with fully doped AlGaAs-based distributed Bragg reflectors (DBR) was investigated. We find a tradeoff between photon lifetime and gain nonlinearity for maximizing the optical bandwidth, leading to the optimum aperture size close to 4-6 μm. In spite of the reduced photon lifetime (from 4 ps to 1 ps), the excess damping caused by the current-induced self-heating limits the ultimate modulation bandwidth for the given VCSELs design at 24-25 GHz. Further improvement in high frequency characteristics can be facilitated by decrease of the heat generation and improvement of the heat removal from the active region as well as by proper engineering of the scattering loss at the oxide aperture while keeping the low capacitance optimizing design of the oxide aperture.